Sex-Dependent Outcome of Hepatitis B and C Viruses Infections: Synergy of Sex Hormones and Immune Responses? - Ruggieri, Anna; Gagliardi, Maria Cristina; Anticoli, Simona (Frontiers in Immunology, 2018)
Hepatitis B (HBV) and C (HCV) are hepatotropic viruses that differ for their genomic content, life cycle and molecular prognosis. HBV and HCV establish chronic lifespan infections that can evolve to fibrosis, cirrhosis and hepatocellular carcinoma (HCC). This malignant liver cancer affects more commonly male patients than females, with a male-to-female incidence ratio of 2:1 up to 7:1. Sex significantly contributes to shape the immune responses, concurring to differences in the pathogenesis of infectious diseases, in male and female patients. Females usually develop more intense innate, humoral and cellular immune responses to viral infections and to vaccination compared to male subjects. Sex hormones, in turn, differentially affect the immune responses to viruses, by specific binding to the hormones receptors expressed by immune cells. In general, estrogens have immune-stimulating effect, while androgens are immune-suppressing. However sex hormones, such as androgen, can also directly interact with HBV genome integrated into the cell nucleus and activate transcription of HBV oncoprotein. On the other side, estradiol and estrogen receptors protect liver cells from inflammatory damage, apoptosis and oxidative stress, which contribute to fibrosis and malignant transformation preceding HCC. In HCV associated cirrhosis and HCC the decreased expression of estrogen receptor alfa (ER) in male patients may explain the worse outcome of HCV infection in men than in women. The synergistic action of male and female sex hormones and of immune response, together with viral factors, partly explain the mechanisms of sex/gender disparity in the outcome and progression of hepatitis viruses infection.